Double pelvic osteotomy for the treatment of hip dysplasia in young dogs - Vezzoni, A.; Boiocchi, S.; Vezzoni, L.; Vanelli, A. B.; Bronzo, V. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
The aim of this study was to evaluate the feasibility of the double pelvic osteotomy (DPO) (osteotomy of the ilium and pubis) to treat clinical cases of hip dyplasia in young dogs instead of performing a triple pelvic osteotomy (TPO) (osteotomy of the ilium, pubis, and ischium). Candidates for DPO were 4.5- to nine-month-old dogs with coxofemoral joint subluxation and laxity, indicative of susceptibility to future development of severe hip dysplasia. The angle of reduction (AR) and angle of subluxation (AS) with Ortolani's sign, Norberg angle (NA), percentage of femoral head (PC) covered by the acetabulum, and the pelvic diameters and their relationships were measured clinically and radiographically before and after surgery. The surgical technique was similar to the TPO technique, but excluded ischiatic osteotomy. A DPO was carried out in 53 joints of 34 dogs AR and AS values immediately postoperatively and at the oneand two-month follow-up examinations were significantly lower than the preoperative values (p <0.01). The complications en-countered were mainly represented by implant failure (3.5%), partial plate pull-out (9.4%), and incomplete fracture of the ischial table (7.5%). Changes in PC and NA values obtained immediately after surgery and at the first and second follow-up examinations were significantly greater (p <0.01 both) than values obtained before surgery. Sufficient acetabular ventroversion was achieved to counteract joint subluxation and the modifications of AR and AS. The NA and PC direct postoperative values reflected a significant improvement in the dorsal acetabular coverage.Clinical relevance: Restoration of normal joint congruity (PC from 50 to 72%) and maintenance of the pelvic geometry without pelvic narrowing were the most intriguing features of DPO. The complications observed were greatly reduced when using dedicated DPO plates. Based on our experience, the morbidity after unilateral and bilateral DPO was lower than after TPO because elimination of the ischiatic osteotomy allowed for increased stability of the pelvis. The surgical technique of DPO was a little more demanding than TPO because of the difficulty in handling and rotating the acetabular iliac segment, but this difficulty was offset by elimination of ischial osteotomy.
Keywords: Juvenile hip dysplasia; DPO; TPO; corrective pelvic osteotomy; double pelvic osteotomy; triple pelvic osteotomy